2022
DOI: 10.3389/fonc.2022.917862
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and Invasion in Oral Squamous Cell Carcinoma Cells Exposed to Electronic Cigarette Vapor Extract

Abstract: Electronic cigarettes (eCig) represent a new avenue of tobacco exposure that involves heating oil-based liquids and the delivery of aerosolized flavors with or without nicotine, yet little is known about their overall health impact. The oral cavity is an anatomic gateway for exposure that can be compromised by activating myriad of signaling networks. Oral squamous cell carcinoma (OSSC) is a common malignancy affecting 30,000 people in the United States each year. Our objective was to determine the impact of eC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…That was also found in a similar study among university students in Jordan, where most students think that e-cigarette smoking is safer than conventional cigarette smoking [ 11 ]. In fact, e-cigarettes vapor is considered very harmful and is linked to oral squamous cell carcinoma [ 33 ]. Moreover, the nicotine contained in e-cigarettes is not only addictive, but can also lead to mouth cancer [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…That was also found in a similar study among university students in Jordan, where most students think that e-cigarette smoking is safer than conventional cigarette smoking [ 11 ]. In fact, e-cigarettes vapor is considered very harmful and is linked to oral squamous cell carcinoma [ 33 ]. Moreover, the nicotine contained in e-cigarettes is not only addictive, but can also lead to mouth cancer [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…These included elevated levels of secreted soluble inflammatory mediators (IL-1α, IL-1β, IL-2, IL-4, IL-6, IL-8, IL-10, IL-12p70, IL-13, tumor necrosis factorα, interferon-γ, CCL-5, CXCL-10, MCP-1, matrix metalloproteinase [MMP]-2, MMP-9, MMP-13, MUC5AC, MUC5B), increased expression of genes or proteins involved in inflammatory signaling (ERK1/2, p38, COX-2, JNK, and NF-kB), and enrichment of gene sets or pathways associated with inflammatory processes. 16,18,25,28,30,35,40,[42][43][44][45][46]49,53,62 Genotoxicity was seen primarily in the oral cavity, but also in the oropharynx and larynx, and was detected by increased DNA fragmentation, adducts, double-or single-strand breaks, appearance of micronuclei or metanuclear abnormalities, or increased expression of genes or proteins involved with DNA damage or repair pathways. 14,19,[22][23][24][25]27,32,51 Histological changes associated with acute and subchronic e-cigarette aerosol exposure in animal models were seen in the oral cavity, submandibular gland, nasal cavity, larynx, and trachea; however, the majority of these changes were considered adaptive and resolved following a recovery period.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, flavoring compounds associated with common flavor names (eg, fruit) often vary across brands, which precludes accurate comparisons of their toxicological impact. Our review found 11 studies 14,17,18,22,28,32,34,39,52,60,64 that directly compared flavors against one another; however, only menthol and tobacco were included in more than 2 studies. Notably, tobacco flavoring appeared to be generally less harmful than the other flavors studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations